Hindlimb muscle representations in mouse motor cortex defined by viral tracing - Maurer, Lauren; Brown, Maia; Saggi, Tamandeep; Cardiges, Alexia; Kolarcik, Christi L. (Frontiers in Neuroanatomy, 2023)
Introduction Descending pathways from the cortex to the spinal cord are involved in the control of natural movement. Although mice are widely used to study the neurobiology of movement and as models of neurodegenerative disease, an understanding of motor cortical organization is lacking, particularly for hindlimb muscles. Methods In this study, we used the retrograde transneuronal transport of rabies virus to compare the organization of descending cortical projections to fast- and slow-twitch hindlimb muscles surrounding the ankle joint in mice. Results Although the initial stage of virus transport from the soleus muscle (predominantly slow-twitch) appeared to be more rapid than that associated with the tibialis anterior muscle (predominantly fast-twitch), the rate of further transport of virus to cortical projection neurons in layer V was equivalent for the two injected muscles. After appropriate survival times, dense concentrations of layer V projection neurons were identified in three cortical areas: the primary motor cortex (M1), secondary motor cortex (M2), and primary somatosensory cortex (S1). Discussion The origin of the cortical projections to each of the two injected muscles overlapped almost entirely within these cortical areas. This organization suggests that cortical projection neurons maintain a high degree of specificity; that is, even when cortical projection neurons are closely located, each neuron could have a distinct functional role (controlling fast- versus slow-twitch and/or extensor versus flexor muscles). Our results represent an important addition to the understanding of the mouse motor system and lay the foundation for future studies investigating the mechanisms underlying motor system dysfunction and degeneration in diseases such as amyotrophic lateral sclerosis and spinal muscular atrophy.